Evaluation of the behavior of rabies main indicators in the province of Chucuito, Puno, Peru - Ferro Mayhua , Felix Pompeyo; Ferro-Gonzales, Polan Franbalt; Rossel Bernedo , Luis Jhordan; Ticona Carrizales , Lucio; Zanabria Huisa, Victor Meliton (Journal of the University of Zulia, 2021)
Rabies, by definition, is an acute and fatal encephalomyelitis that affects man and a large number of domestic and wild animals. The present research aims to evaluate the main rabies indicators in Chucuito, a province of the Puno-Peru Region; the analysis of the data registered in the forms of the zoonosis sanitary strategy has been carried out in the Environmental Health Unit of the Health network, Chucuito. It is concluded that, during the evaluated years, there was only one outbreak of human rabies in 2010, coinciding with a low coverage of canine rabies vaccination (53%), and with a case of canine rabies in the same year. On the other hand, three cases of canine rabies were reported in unvaccinated dogs, the bitten people were treated for the most part, along with adequate control of the dogs.